2016
DOI: 10.14411/fp.2016.023
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of avian haemosporidian parasites from raptor birds in Turkey, with molecular characterisation and microscopic confirmation

Abstract: Avian haemosporidians are common vector-borne blood parasites that have been reported in birds all over the world. Investigations of avian haemosporidian parasites are conducted mainly on passerine birds. However, studies that focus on non-passerine avian hosts are important for our understanding of the true diversity, host specificity and genetic variability among these widespread parasites. In the present study, blood samples from a total of 22 raptor birds belonging to two orders, two families and six speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
3
27
1
1
Order By: Relevance
“…Our low detection rate of Haemoproteus (0.16% as compared to 5% found by Young and Proudfoot [2014]) may be because we used the same primer to screen for Haemoproteus and Plasmodium. It is possible that these primers are a better match to Plasmodium cyt-b, thereby causing us to underestimate Haemoproteus infections as has been suggested by other researchers (Ciloglu et al 2016, Hanel et al 2016, Meixell et al 2016. With regard to species richness, we cannot compare our results to that of Young and Proudfoot (2014) because they did not identify haemosporidians beyond the genus level.…”
Section: Parasite Type Prevalence and Species Richnessmentioning
confidence: 83%
See 2 more Smart Citations
“…Our low detection rate of Haemoproteus (0.16% as compared to 5% found by Young and Proudfoot [2014]) may be because we used the same primer to screen for Haemoproteus and Plasmodium. It is possible that these primers are a better match to Plasmodium cyt-b, thereby causing us to underestimate Haemoproteus infections as has been suggested by other researchers (Ciloglu et al 2016, Hanel et al 2016, Meixell et al 2016. With regard to species richness, we cannot compare our results to that of Young and Proudfoot (2014) because they did not identify haemosporidians beyond the genus level.…”
Section: Parasite Type Prevalence and Species Richnessmentioning
confidence: 83%
“…Most studies of haemosporidian parasites found in birds during migration are conducted on passerine species (Passeriformes) (Manwell and Herman 1935, Rintamäki et al 1998, Garvin et al 2006, Krone et al 2008) and waterfowl (Anseriformes) (Figuerola andGreen 2000, Reeves et al 2015), with much less attention given to raptors (Accipitriformes, Falconiformes, and Strigiformes) (Krone et al 2008, Clark et al 2014, Ciloglu et al 2016. Perhaps fewer studies are conducted on raptors because they are at the top of the food chain and, thus, there are fewer species that provide opportunities for research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission for T. avium remains still unclear with various blood-sucking insects mentioned as possible vectors (Votypka et al, 2002). Haemosporida are generally considered as pathogens with a low pathogenicity and harmless in bird populations (Wiersch et al, 2007;Ciloglu et al, 2016), but several studies demonstrated different costs on life-history traits associated with Haemosporida infections: Haemosporidian parasites can affect the body condition (Valkiūnas et al, 2006), reproductive success (e.g. Hunter et al, 1997;Merino et al, 2000;Marzal et al, 2005;Tomás et al, 2007a;Knowles et al, 2010) and the survival (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Leucocytozoon lineages are deposited in the avian haemosporidian parasite database MalAvi (Bensch et al 2009, MalAvi database accessed August 2018). In addition, molecular surveys vastly improved our understanding about the host specificity of avian haemosporidian infections (Ciloglu et al, 2016). The Haemosporida occupy niches that vary from extreme host generalization to extreme host specialization (Okanga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%